Identification of Structural Damage in Frame Bridge Using Mode Shape Curvature: Simulation on Laboratory-Scale Frame Bridge - Irawan, Djoko; Suswanto, Budi; Habieb, Ahmad Basshofi; Fitriyah, Dita Kamarul (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2024)
Most bridge construction is dominated by steel bridges with various designs and structural types. The choice of steel as a material is due to its known strength, durability, and resistance to damage. However, if maintenance activities on steel bridges are lacking, there is a potential for damage or even failure of the structure. Structural failure can result in economic losses for the country, and more importantly, it can pose a threat to human safety. Therefore, there is a need for monitoring activities to assess the structural health. The development of monitoring activities in the last decade includes the Structural Health Monitoring System (SHMS). To address the challenges of SHMS, various methods are being researched. Non-Destructive Testing (NDT) methods are considered the best choice as an inspection tool, being perceived as easy, and effective in detecting and diagnosing various structural issues. Hence, in research, the detection of damage locations in steel bridge structures is carried out using the Mode Shape Curvature (MSC) method with the assistance of an accelerometer sensor. The MSC method contributes to SHM at level II, specifically in detecting the location of damage in the structure. It is observed that in the designed damage scenarios, the MSC index indicates a loss of stiffness with an increase in the MSC value at the damage location.